2015
DOI: 10.1103/physrevb.92.020403
|View full text |Cite
|
Sign up to set email alerts
|

Driving magnetic skyrmions with microwave fields

Abstract: We show theoretically by numerically solving the Landau-Lifshitz-Gilbert equation with a classical spin model on a two-dimensional system that both magnetic skyrmions and skyrmion lattices can be moved with microwave magnetic fields. The mechanism is enabled by breaking the axial symmetry of the skyrmion, for example through application of a static in-plane external field. The net velocity of the skyrmion depends on the frequency and amplitude of the microwave fields as well as the strength of the in-plane fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 40 publications
3
87
0
1
Order By: Relevance
“…We have confirmed that not only the crystallized magnetic skyrmions (skyrmion crystal) but also isolated skyrmions in ferromagnets can be excited resonantly by application of a microwave field, which offers a better experimental feasibility because a lot of ferromagnet/heavy-metal bilayer systems turned out to host magnetic skyrmions as topological defects [28,[54][55][56]. Recent theoretical studies revealed that activation of the skyrmion breathing mode under application of a magnetic field inclined from the vertical direction induces translational motion of the skyrmions [57][58][59], which provides a means to drive magnetic skyrmions electrically with a low energy consumption. Our finding provides a promising technique to manipulate noncollinear magnetic textures with a great efficiency that have potential applications in memory, logic, and microwave devices.…”
Section: Discussionsupporting
confidence: 62%
“…We have confirmed that not only the crystallized magnetic skyrmions (skyrmion crystal) but also isolated skyrmions in ferromagnets can be excited resonantly by application of a microwave field, which offers a better experimental feasibility because a lot of ferromagnet/heavy-metal bilayer systems turned out to host magnetic skyrmions as topological defects [28,[54][55][56]. Recent theoretical studies revealed that activation of the skyrmion breathing mode under application of a magnetic field inclined from the vertical direction induces translational motion of the skyrmions [57][58][59], which provides a means to drive magnetic skyrmions electrically with a low energy consumption. Our finding provides a promising technique to manipulate noncollinear magnetic textures with a great efficiency that have potential applications in memory, logic, and microwave devices.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, all the parameters are with reduced units for simplicity and set to be ħ=1/6, γ=6, S=1 and the lattice constant a=1, respectively. To convert the parameters to SI units, one should consider the coefficients the magnetic field h=J 1 /(ħγS), time t=6ħS/J 1 , and the velocity v=J 1 a/(6ħS) [20]. If one take J 1 =0.1 meV, S=1 and a=0.5 nm, the magnetic field h∼0.8 T, the strength of h-gradient ∇h∼10 −4 T/a, and v∼12 m s −1 are estimated.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Low-frequency collective modes of the two-dimensional Skyrmion lattice are well understood theoretically [19][20][21] and demonstrated by microwave experiments [22][23][24]. They arise from either the breathing mode (when Skyrmions expand and contract periodically) or the small cyclotron-like motion of the center of mass of the Skyrmions.…”
mentioning
confidence: 99%
“…Instead, layer-by-layer analysis of the Skyrmion density variation over time revealed some oscillatory behavior reminiscent of the Skyrmion's center-of-mass motion in the two-dimensional crystal. Real-time calculations for the two-dimensional Skyrmion lattice done in the past assumed a large Skyrmion radius [19,22,23]. The slow collective motion was easy to identify, typically by visual inspection of the real-time video generated from solving the LLG equation.…”
mentioning
confidence: 99%